China's reform in global perspective - Wong, John, 1939-; Bo, Zhiyue (Series on contemporary China, 2010)
This book provides a fascinating perspective of the experiences of China's reform in the past three decades by focusing on China's interaction with and learning from the external world in her unprecedented efforts to reform and open up. After three introductory chapters on broad scope of reform in the political, economic, and social realms, this book deals with lessons from the Eastern Bloc, China's reform in East Asian context, and China and the developed world. The book concludes with two chapters looking to the future of China's political and economic development. In the existing literature.